Platelet aggregation in chronic idiopathic thrombocytopenic purpura. Issue 12 (December 1978) - Heyns, A D; Fraser, J; Retief, F P
Abstract : A method for washing platelets by albumin density gradient separation has been modified to prepare platelet rich plasma of thrombocytopenic patients for platelet aggregation studies. The concentration procedure, consisting of centrifuging platelets into a specific gravity gradient between plasma and 40-45% aqueous solution of bovine albumin, does not affect platelet aggregation adversely. Platelet aggregation in eight patients with chronic idiopathic thrombocytopenic purpura was determined by this method. On the basis of the results the patients could clearly be divided into two groups: four patients with normal aggregation and four with a qualitative platelet defect. In contrast to the other patients, the group with an in vitro platelet functional defect all had more prolonged bleeding times and the presence of a serum antiplatelet antibody.